Technetium-99m-indocyanine green versus technetium-99m-methylene blue for sentinel lymph node biopsy in early-stage endometrial cancer. Issue 3 (27th January 2020) - Cabrera, Silvia; Bebia, Vicente; Franco-Camps, Silvia; Forcada, Cristina; Villasboas-Rosciolesi, Diego; Navales, Ignacio; Pérez-Benavente, Assumpció; Gil-Moreno, Antonio
Abstract : Introduction: The low accuracy of pre-operative imaging techniques for prediction of nodal status strengthens the relevance of sentinel lymph node (SLN) biopsy in endometrial cancer, although the optimal method for its detection is still under investigation. The increasing use of indocyanine green (ICG) has aroused concern about its enhanced visualization of lymphatic channels, which could lead to a specimen that is thought to be nodal tissue not subsequently yielding a lymph node on pathologic analysis ('empty node packet'). Our main objective was to compare the overall and bilateral detection rates for SLN biopsy using two combined techniques: technetium-99m-ICG (Tc-99m-ICG) versus technetium-99m-methylene blue (Tc-99m-MB). Our secondary aim was to compare the 'empty node packet' rates between the two cohorts. Methods: A prospective, non-randomized, single-center trial including patients diagnosed with endometrial cancer (any grade or histology) in pre-operative early stage, and operated on between February 2017 and July 2019. All tracers were injected intracervically. Pelvic and aortic lymphadenectomy were performed on patients at intermediate or high risk of recurrence pre-operatively. All SLNs were sent for intra-operative frozen section and afterwards processed following an ultrastaging protocol. Results: Eighty-four patients were included, 58% (n=49) in the Tc-99m-MB group and 42% (n=35) in the Tc-99m-ICG group. Overall detection rate was 93% and was not statistically different between the two groups. A better bilateral detection rate was observed among Tc-99m-ICG patients (69% vs 41%, p=0.012). The 'empty node packet' rate was 4% in the Tc-99m-ICG cohort and 0% in the Tc-99m-MB cohort (p=0.032). Discussion: Tc-99m-ICG is a feasible, safe technique for SLN biopsy in early-stage endometrial cancer, and appears to be superior in terms of bilateral detection to Tc-99m-MB. The addition of Tc-99m to ICG could decrease the rate of 'empty node packets' and better define the anatomic location of SLNs in patients with endometrial cancer.